Finance and Development, March 1968. (Finance and Development; Finance and Development, 1968)
This paper examines the export performance of developing countries. Taking any recent period, for example the past 15 years, the growth rate in export earnings for individual countries has varied from substantial year-to-year increases to absolute declines. Countries with growth rates as high as 13 percent per year include Greece, Jamaica, and Peru, while at the other end of the spectrum are Bolivia, Paraguay, and Uruguay, whose export earnings declined in absolute terms.